1994
DOI: 10.2307/3432237
|View full text |Cite
|
Sign up to set email alerts
|

Oxidants, Antioxidants, and Respiratory Tract Lining Fluids

Abstract: Respiratory tract lining fluids (RTLFs) are a heterogeneous group of substances covering the respiratory tract epithelial cells (RTECs) from nasal mucosa to alveoli. Antioxidant contained in the RTLFs can be expected to provide an initial defense against inhaled environmental toxins. The major antioxidants in RTLF include mucin, uric acid, protein (largely albumin), ascorbic acid, and reduced glutathione (GSH). RTLF antioxidants can be augmented by such processes as transudation/exudation of plasma constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 48 publications
3
155
1
2
Order By: Relevance
“…This is probably why the initial histological abnormality of CF fetuses occurs in submucosal glands (1,2), because in the absence of SCN Ϫ from the serous cells, unconsumed H 2 O 2 would be expected to irritate and harm the secreting glands, leading to inflammation and injuries. Duox activity indirectly stimulates mucin expression by epithelial cells (37); and mucin has a protective effect in that it scavenges ROS, including H 2 O 2 (38). The tissue-harming effects of H 2 O 2 may contribute to the inflammation observed in the digestive system and the lungs of CF patients in the absence of clinical infection.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably why the initial histological abnormality of CF fetuses occurs in submucosal glands (1,2), because in the absence of SCN Ϫ from the serous cells, unconsumed H 2 O 2 would be expected to irritate and harm the secreting glands, leading to inflammation and injuries. Duox activity indirectly stimulates mucin expression by epithelial cells (37); and mucin has a protective effect in that it scavenges ROS, including H 2 O 2 (38). The tissue-harming effects of H 2 O 2 may contribute to the inflammation observed in the digestive system and the lungs of CF patients in the absence of clinical infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke/air particulate-mediated lung injury Alveolar cells are normally covered in a thin protective layer of epithelial fluid, which is rich in antioxidants such as GSH [194]. It has been reported that incubation with extracellular GSH and increasing intracellular GSH levels protect against oxidant stress in alveolar type II cells [7,195].…”
Section: Antioxidant Protective Genesmentioning
confidence: 99%
“…Much more recently there has been much interest in the composition of the epithelial lining fluid (ELF) of the lung, that part of the structure which is in direct contact with the inhalant mix, above and beyond the physiology and pathophysiology of surfactants (Collard et al, 2004;Cross et al, 1994;Nishiki et al, 1976;Schock et al, 2001). Catalase is one ingredient of epithelial lining fluid but as the probable total volume of this thin layer in the adult lung is less than 10 ml spread across a surface area in excess of 880,000 cm² (Cross et al, 1994), and appears in the ELF only late in development ( Kaarteenaho-Wiik and Kinnula, 2004), this is not much of a defense for a premature newborn experiencing a sudden order of magnitude increase in pulmonary oxygen content, from 10-12 up to 110-120 Torr.…”
Section: Discussionmentioning
confidence: 99%